A. A. ZINOVIEV ON THE TRANSFORMATION OF THE SOVIET MANAGERIAL ELITE - E. M. Amelina (Publishing House of the State University of Management, 2021)
The article analyses the views of the famous Russian sociologist and philosopher, A. A. Zinoviev (1922–2006) on the Soviet administrative elite and the stages of its social and spiritual evolution. The paper reveals the ideas of the sociologist about the ideological basis of the formation of this elite, the degree of its organic nature to society. The author investigates identified by A. A. Zinoviev, social types of managers inherent in the early and late periods of the life of the USSR. The study shows that the Leninist and Stalinist leaders, according to the sociologist’s worldview, were inspired by the spirit of communism, widely attracted people to government and controlled the growth of the bureaucracy. The article reveals the ideological and social meaning of de-Stalinization as an inevitable, but morally defective administrative step, from the position of a philosopher. The paper identifies the main characteristics of the Brezhnev and Gorbachev management elite, as a privileged stratum cut off from the people, who have lost faith in communist ideals and are ready for capitalist transformation. The author shows that the subsequent regressive evolution of the country A. A. Zinoviev considers it as a consequence of the death of the spirit of communism, that is, the state of human souls that were characteristic of the first stages of the life of the Soviet administrative elite, and raised the spiritual life of people to the unattainable heights of historical romance.